Deposition of borophosphosilicate glass films using the TEOS – dimethylphosphite – trimethylborate system - Turtsevich, A. S.; Nalivaiko, O. Yu. (Technology and design in electronic equipment, 2015)
Modernization of horizontal low pressure deposition system has been performed. The liquid source delivery system using the bubblers has been developed. The PSG and BPSG film deposition processes and film properties using TEOS – Dimethylphosphite – TEB system have been studied. It is shown that the use of dimethylphosphite allows varying the phosphorus concentration in the wide range. It is found that the optimal range of the total boron and phosphorus concentration ensuring the acceptable topology planarity and resistance to defect formation during storage is 8.7 – 0.3 wt% when the phosphorus concentration is 3.0 – 3.8 wt%. It is found that at use of the TEOS – DMP – TEB system the depletion of the phosphorus concentration along the reaction zone does not occur, and the total dopant concentration is practically constant. At the same time, the deposition rate of BPSG films is 9.0 – 10.0 nm/min and the good film thickness uniformity is ensured. The as-deposited films have “mirror-like surface” that is proof of minimal surface roughness. The BPSG films with optimal composition are characterized by the reduced reaction capability against atmospheric moisture.